Revisiting and Integrating Residents’ Perceptions Towards Tourism Development in urban - Nyikana, Siyabulela; Mchunu, Ayanda; Mazibuko, Busisiwe (Turizam, 2024)
This study sought to determine residents’ perceptions towards tourism development and the subsequent impacts of tourism in South Africa. Tourism’s impacts on residents have been a topical issue in existing literature given that they can offer guidance for planners in terms of development trajectories. This is because tourism is widely associated with both negative and positive impacts on residents, depending on the destination’s life cycle and other factors. Thus, Soweto as South Africa’s most visited township and a place where tourism is seen as a strategic tool for socio-economic development was selected as an ideal case study for this research. A positivist, quantitative research approach was employed in targeting residents (n=241) using a systematic random sampling method. Data was analysed through IBM SPSS 24 and key findings revealed that, on the whole, residents are involved directly or indirectly in tourism and generally support its development. Additionally, it was found that residents have largely positive feelings towards tourism and its development in the area although nuances were there regarding tourism recently highlighting the economic gaps between the poor and the rich. The government was also criticised for failing to increase education about tourism among residents so that they can effectively benefit from it. It was also suggested that tourism compromises the authenticity of heritage and cultural activities in the area, whilst also resulting in the increased prices of goods and services for locals. The study recommends that there be more collaboration with the residents such that they would be able to capitalize on the opportunities presented by tourism. Moreso, regular dialogue with residents around tourism development in their area ought to strengthen the position of tourism as a socio-economic tool for local development and growth. The study therefore ultimately contributes to existing theoretical debates around the effective management of tourism for the betterment of society.